(untitled) (AYUSHDHARA, 2017)
Ardhavabhedaka is one among the 11 types of Shirorogas described in Ayurvedic classical texts. It is a type of headache where pain is localized to one half of the head. It can be correlated with migraine based on the similarity in etiology, pathology, symptoms and treatment principles. This study is conducted with the aim to compare the effect of ‘Sharkara Mishrita Dugdha Nasya’ and ‘Murchita Gritha Nasya’ in the management of Ardhavabhedaka. Two groups of 15 patients each were administered these two types of Nasya drugs for seven days. Patients were assessed on the basis of clinical parameters. Results show good effect on all symptoms of Ardhavabhedaka in both groups but Murchita Ghrita Nasya show better effect than Sharkara Mishrita Dugdha Nasya. Among 15 patients in Group-A, 7 patients (36%) showed good response and among 20 patients in Group-B, 3 patients (16 %) showed good response after the treatment. The response obtained after 28 days of treatment and the study reveals that in Group – B Murchita Ghrita Nasya shows very good response in treating the Ardhavabhedaka. Sharkara acts as Vatapitta hara, Dugdha & Murchita Ghrita acts as Tridoshaghna.